Pharmacogenomic and Bioinformatic Insights into ACE Gene Variants and Their Influence on ACE Inhibitor Response in Hypertension - Amukti, Danang Prasetyaning; Ria Indah Pratami; Ismyama, Dian Farida; Puspitasari, Ade; Herlina, Tetie (CV. Nusantara Scientific Medical, 2025)
Response to angiotensin-converting enzyme inhibitors (ACEIs)-based antihypertensive therapy varies between individuals, which is largely influenced by genetic factors. The ACE gene has several polymorphisms that can affect enzyme levels and therapeutic efficacy. This study aims to explore the relationship between genetic variations in the ACE gene and response to captopril, lisinopril, ramipril, and enalapril in hypertensive patients. This study used a bioinformatics and pharmacogenomics approach by analyzing data from PharmGKB, Ensembl, and GTEx Portal. Genetic polymorphisms were analyzed to evaluate their association with ACEI efficacy using a descriptive statistical approach. Results: Four single nucleotide polymorphisms (SNPs) in the ACE gene were found to be associated with response to ACEI. Variants rs4291 and rs1799752 were associated with captopril efficacy, where the AA genotype showed a decrease in the severity of renal failure. The rs1799752 variant was also associated with lisinopril and enalapril, with the DD genotype providing greater blood pressure reduction. In addition, rs4359 and rs4344 were correlated with the efficacy of ramipril, especially in the CC+TT and AA+GG genotypes. Genetic variation in the ACE gene plays a role in determining the response to ACEI therapy. Pharmacogenetic approaches have the potential to improve the efficacy and safety of antihypertensive treatment.